Interpretation of Agricultural Pest Problem Handling System in Usada Wisada Pari Scripture - Jayendra, Putu Sabda; Ekasani, Kadek Ayu; Saitya, Ida Bagus Subrahmaniam; Mahendra, Made Wahyu (Religious (Online), 2021)
The knowledge of cultivation and the methods of treating and solving pest problems naturally without neglecting the local culture has been an inseparable aspect of Balinese agricultural life, which is known for its irrigation system called subak. This study aims to examine agricultural scripture named Usada Wisada Pari from two perspectives. First, this study examines the types of pests and its countermeasure. Secondly, it is important to study the lexicon form of these pests. This study shows that the types of rice pests in the Usada Wisada Pari text are categorized into two types, namely animals and plants. The countermeasure consists of natural ritual elements from plants and incantations. Furthermore, this research also shows that all kinds of plague and agricultural pests, along with ways to overcome them, reflect the very strong Shivaistic teachings. All kinds of diseases, countermeasures and prevention are described as the authority of Lord Shiva as the god of destruction in the Hindu concept. It can be concluded that the scripture of Usada Wisada Pari is a text that provides knowledge about rice pest antidotes in an environmentally friendly and holistic manner because it involves natural and religious elements. This study is expected to contribute both to academics or future researchers as well as to the public. It is hoped that academics and researchers can use this present study as a source and expand as well as deepen the object of study based on ethnoagriculture. Meanwhile, the general public can increase their knowledge regarding alternative management of agricultural epidemics in synergy with nature and local wisdom.